PENINGKATAN STRATEGI PEMASARAN DAN BRANDING UMKM DESA PENTUR KABUPATEN BOYOLALI MELALUI DIGITAL MARKETING - Andriani Kusumaningrum; Sri Harjanto; Sri Siswanti; Setiyowati Setiyowati; Mita Purwati; Retno Tri Vulandari (ABDI MAKARTI, 2023)
Economically, most of the residents of Pentur Village are farmers, both working in paddy fields and fields, apart from that, it is also a center for the bamboo woven craft industry which is the livelihood of some of the residents. In fact, Pentur village also has a fairly well-known foundation called "Tumpi Redhouse" which was founded on July 16 2012. In this library there are 2500 book collections, hundreds of film collections, various magazines and reference books. Apart from being a place to read, this library also holds various community empowerment activities such as agricultural activities and MSME groups. Several arts live in this village, various traditional ceremonies such as cleaning the village with shadow puppet performances are still held every year, apart from that, reog art, music and painting are also the breath of artistic activities in this village. The aim of this service is to implement visuals in content and digital marketing formats to improve the economy of Pentur village. Methods for implementing the service include content creator and digital marketing workshops for MSMEs in Pentur village. The resulting output is the implementation of the workshop. At the end of this program, activities will be published via print and online media.